Components of the gut microbiota diet and its influence on the reduction of complications in patients with chronic chronic diseases (Research, Society and Development, 2022)
Introduction: Considering that acute and chronic CKD consist of high levels of mortality and mobility among their patients, research is carried out on dietary components in the intestinal microbiota and their influence on the reduction of complications in patients with chronic kidney diseases. Objective: This study aims to show that the intestinal microbiota has an important role in its functioning for health and influence in the reduction of complications in patients with chronic kidney diseases. Methodology: The method used in this study is the literature review, using a basic method of qualitative, descriptive-exploratory literature review. Results: The intestine is an organ that makes up the gastrointestinal tract, divided into two segments: small and large. As fundamentals functions capabilities, it carries out digestion and absorbs nutrients, water and electrolytes from the diet, production of enzymes and mucus, finally the development that forms the feces. Discussion of the results: Therefore, it is necessary to describe the components of Diet in the Intestinal Microbiota and its influence on the reduction of complications in patients with Chronic Kidney Diseases, elaborating nutritional guidelines for patients with kidney disease, highlighting the interrelationship of the intestinal microbiota and the Chronic Kidney Disease and through the method Systematic literature review Conclusion: it is concluded that having a balanced diet is important for patients with chronic kidney disease, so it must be composed of foods that help them to have a quality life.